13+3k=11
-Move constant to the right-hand side and change its sign
3k=11-13
Calculate the difference
3k=-2
Divide both sides by 3
K= -2/3
11) -x + y = -1 ; 2x - y = 0
y = -1 + x ; 2x - (-1+x) = 0 ⇒ 2x + 1 - x = 0 ⇒x = -1
y = -1 + (-1) ⇒ y = -2
12) -2x + y = -20 ; 2x + y = 48
y = -20 + 2x ; 2x + (-20 + 2x) = 48 ⇒ 2x -20 + 2x = 48 ⇒ 4x = 48 + 20
4x = 68 ⇒ x = 68/4 ⇒ x = 17
y = -20 + 2(17) ⇒ y = -20 + 34 ⇒ y = 14
13) 3x -y = -2 ; -2x + y = 3
y = 3 + 2x ; 3x - (3 + 2x) = -2 ⇒ 3x - 3 - 2x = -2 ⇒ x = -2 + 3 ⇒ x = 1
y = 3 + 2(1) ⇒ y = 3 + 2 ⇒ y = 5
14) x - y = 4 ; x - 2y = 10
x = 4 + y ; (4 + y) - 2y = 10 ⇒ 4 + y - 2y = 10 ⇒ 4 - y = 10
⇒ -y = 10 - 4 ⇒ -y = 6 ⇒ y = -6
x = 4 + (-6) ⇒ x = 4 - 6 ⇒ x = -2
15) x + 2y = 5 ; 3x + 2y = 17
x = 5 - 2y ; 3(5-2y) + 2y = 17 ⇒ 15 - 6y + 2y = 17 ⇒ -4y = 17 - 15
⇒ -4y = 2 ⇒ y = -2/4 ⇒ y = -1/2
x = 5 - 2(-1/2) ⇒ x = 5 + 2/2 ⇒ x = 5 + 1 ⇒ x = 6
The unknown number equals x. (you can use any other letter)
the unknown number is being subtracted by 3.
x-3.
now if it is no more than 2, it must be less than 2,
x-3<2
hope this helps
Answer:
x = 4, y = 2
Step-by-step explanation:
Start by multiplying the first equation by 2:
2x + 2y = 12 --> 4x + 4y = 24
Subtract the second from the first:
4x + 4y = 24
- 5x + 4y = 28
4x - 5x = -x
4y = 4y = 0
24 - 28 = -4
so you end with -x + 0 = -4
Solve for x to get x = 4
Plug x = 4 back into 2x + 2y = 12 to find y.
2(4) + 2y = 12
8 + 2y = 12
2y = 4
y = 2
Answer:
I am 99.99% sure it is the first one